2022
DOI: 10.3389/fonc.2022.1028664
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts-derived lncRNA signature as a putative biomarker in breast cancer

Abstract: Long noncoding RNAs (lncRNAs) have been reported to play a key role in regulating tumor microenvironment and immunity. Cancer-associated fibroblasts (CAFs) are abundant in many tumors. However, the functional and clinical significance of lncRNAs specifically expressed in CAFs has not been fully elucidated. In this study, we identified a list of 95 CAF-specific lncRNAs (FibLnc), including HHLA3, TP53TG1, ST7-AS1, LINC00536, ZNF503-AS1, MIR22HG, and MAPT-AS1, based on immune cell transcriptome expression profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For ZNF503-AS1, high levels of ZNF503-AS1 in plasma are associated with a high prevalence of diabetic retinopathy [20]. Moreover, ZNF503-AS1 can also serve as a potential biomarker for breast cancer and colorectal cancer [21,22]. In previous studies, SPINT1-AS1 has been confirmed as a potential biomarker for renal clear cell carcinoma [23], Furthermore, it has also been identified as an independent prognostic indicator in pituitary adenoma, colorectal cancer, esophageal squamous cell carcinoma, and melanoma [24][25][26][27].…”
Section: Results Of In Vitro Cell Function Experimentsmentioning
confidence: 99%
“…For ZNF503-AS1, high levels of ZNF503-AS1 in plasma are associated with a high prevalence of diabetic retinopathy [20]. Moreover, ZNF503-AS1 can also serve as a potential biomarker for breast cancer and colorectal cancer [21,22]. In previous studies, SPINT1-AS1 has been confirmed as a potential biomarker for renal clear cell carcinoma [23], Furthermore, it has also been identified as an independent prognostic indicator in pituitary adenoma, colorectal cancer, esophageal squamous cell carcinoma, and melanoma [24][25][26][27].…”
Section: Results Of In Vitro Cell Function Experimentsmentioning
confidence: 99%
“…They found that the high FibLnc score correlated with worse overall survival (OS) in breast cancer patients. Moreover, the FibLnc score was positively associated with immune cell dysregulation score and stronger immune response to anti-PD1 and anti-CTLA4 therapy [65].…”
Section: Cafsmentioning
confidence: 93%